Added prognostic value of longitudinal changes of angiogenic factors in early‐onset severe pre‐eclampsia: a prospective cohort study. (21st July 2020) - Peguero, A; Fernandez‐Blanco, L; Mazarico, E; Benitez, L; Gonzalez, A; Youssef, L; Crispi, F; Hernandez, S; Figueras, F
Abstract : Objective: To assess in women with early‐onset severe pre‐eclampsia whether longitudinal changes in angiogenic factors improve the prediction of adverse outcome. Design: Prospective cohort study. Setting: Maternity units in two Spanish hospitals. Population: Women with diagnosis of early‐onset severe pre‐eclampsia. Methods: Levels of placental growth factor (PlGF), soluble fms‐like tyrosine kinase (sFlt‐) and sFlt‐1/PlGF ratio were measured at admission and before delivery, and average daily change calculated. The association of longitudinal changes of angiogenic factors with the time interval to delivery and with complications was evaluated by logistic and Cox regression. Main outcome measures: Interval to delivery and composite of adverse outcomes. Results: We included 63 women, of which 26 (41.3%) had a complication. Longitudinal changes of sFlt‐1 were more pronounced in complicated pregnancies (median: 1047 versus 342 pg/ml/day; P  = 0.04). On the multivariate analysis, the clinical risk score and sFlt‐1 at admission explained 6.2% of the uncertainty for complication; the addition of sFlt‐1 longitudinal changes improved this to 25.3% ( P  = 0.002). The median time from admission to delivery was 4 days (95% CI 1.6–6.04) in those in the highest quartile of sFlt‐1 longitudinal changes versus 16 days (95% CI 12.4–19.6) in the remaining women (Log‐rank test P  < 0.001). Conclusions: Longitudinal changes in sFlt‐1 maternal levels from admission for confirmed early‐onset severe pre‐eclampsia add to baseline characteristics in the prediction of adverse outcome and interval to delivery. Tweetable abstract: In early‐onset severe pre‐eclampsia, longitudinal changes in sFlt‐1 levels improve the prediction of complications and interval to delivery. Tweetable abstract: In early‐onset severe pre‐eclampsia, longitudinal changes in sFlt‐1 levels improve the prediction of complications and interval to delivery.